Design and application of hydrogen fuel cell hybrid system for digital rail vehicle - QI Fang; CUI Zhousen; ZHANG Chi; YANG Li (机车电传动)
In order to achieve the carbon peaking and carbon neutrality goals and to meet the market demand, CRRC Nanjing Puzhen Co., Ltd. developed a hydrogen energy digital rail vehicle platform, and applied the hydrogen fuel cell hybrid system to digital rail vehicle for the first time. The hydrogen fuel cell hybrid system is one of the key technologies of digital rail vehicle. For the purpose of this paper, the principle of model selection for hydrogen power and energy storage systems were summarized based on the key indicators, such as traction performance, endurance mileage and average power of digital rail vehicle, the scheme of system parameter matching and model selection that meets the actual operational requirements was determined, and an improved power following algorithm based on active following was proposed to keep the fuel cell system operates under high-efficient range during the operation of the vehicle. The test results show that when the energy management method proposed in this paper is adopted, the average hydrogen consumption of digital rail vehicle is about 20 kg per 100 km, and the total carbon emission of each vehicle is reduced by 125 600 kg per year, which fully proves the feasibility of applying the hydrogen fuel cell hybrid power system to digital rail vehicle, and lays the foundation for its extension to other vehicle systems.